Deteriorated biomechanical properties of human hypertrophied septum in response to cardiomyocyte enlargement, overexpressed collagen, and disarrayed microstructures - Copeland, Katherine M.; Chen, Houjia; Chintapula, Uday; Almasian, Milad; Chung, Duc Khang; Taylor, Alan M.; Ding, Yichen; Sharma, Gaurav; Jessen, Michael E.; Hong, Yi; Nguyen, Kytai T.; Peltz, Matthias; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Hypertrophic cardiomyopathy (HCM) is often caused by genetic mutations, resulting in abnormal thickening of ventricular muscle, particularly the septum, and causing left ventricular outflow tract (LVOT) obstruction and inferior cardiac performance. The cell and microstructural abnormalities are believed to be the cause of the altered tissue mechanical properties and inferior performance. However, there is a lack of detailed biomechanical assessments of human hypertrophied septum and a lack of understanding of the structural-mechanical relationship between altered biomechanical properties and cellular hypertrophy, fibrotic overexpression, and microstructural disruptions. In this study, we performed thorough biomechanical and microstructural characterizations on the human hypertrophied septum and compared this with healthy septum. We found that the hypertrophied human septum was stiffer at the initial phase of tissue loading, but less nonlinear, less stiff in the linear region, and much weaker in mechanical strength when compared to the healthy human septum. The fibrosis-induced initial stiffening in the hypertrophied septum paradoxically coexists with compromised mechanical strength and integrity under physiological demands, correlating with the clinical observations of diastolic dysfunction and susceptibility to myocardial damage in HCM patients despite ventricular wall thickening. We also discovered that the human hypertrophied septum had significantly larger stress relaxation and slightly larger creep when compared to healthy septum. Moreover, the abnormal, disorganized cell-collagen microstructures in the hypertrophied septum make short-term stress release more difficult and require longer relaxation times to reach equilibrium. Biaxial testing performed at the initial phase of tissue loading showed that both the healthy septum and hypertrophied septum had nonlinear anisotropic stress-strain behavior and confirmed that, in the longitudinal direction, the hypertrophied septum was stiffer than the healthy septum. Our microstructural quantifications via histology and light-sheet microscopy revealed that (i) the heterogeneous cardiomyocyte enlargement and disarray, combined with disorganized collagen overexpression, create a mechanically inefficient tissue architecture in the hypertrophied septum, and (ii) the observed cell-collagen microstructural disruptions provide mechanistic explanations for the deteriorated biomechanical properties. Our viscoelastic mechanical data and microstructural characterizations build a strong foundation to understand the altered tissue behavior of the hypertrophied septum, the degree of deviation from the normal septum, and the underlying structural mechanisms.